Cooperation self-excited induction generator SEIG from the power - Kasprowicz, A. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents the control of the self-excited induction generator in terms of cooperation with the mains. This made it possible to extend the scope of the system. The proposed system is characterized by very high flexibility of powering receivers as well as the possibility of reselling the produced energy to the grid. The direction of flow of energy to the proposed arrangement can be reversed. This condition occurs in case of shortage of energy produced by the generator SEIG (small wind strength, low water level, high energy requirements). The ability to change the direction of energy flow is ensured by a bilateral converter AC/DC/AC used in the proposed solution. The grid inverter is coupled to the network through an LCL filter. This solution provides a sinusoidal current flow in both directions: power supply and the grid. In the case of complete processing of the power of generator without the cooperation with the grid, the system operates in standalone mode or uninterruptible power supply mode.